Leveraging Blockchain Technology for Test Data Integrity in Regulated Industries - Sridhar Dachepelly (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative potential of blockchain technology in maintaining test data integrity across regulated industries, particularly in finance, healthcare, and pharmaceuticals. The article examines how blockchain’s inherent characteristics address critical challenges in data security, compliance, and operational efficiency. Through analysis of implementation strategies, industry-specific applications, and emerging trends, the article demonstrates how blockchain technology revolutionizes test data management through immutable record-keeping, decentralized architecture, and smart contract automation. The article indicates significant improvements in data security, compliance management, and operational efficiency across all examined sectors, while highlighting the importance of structured implementation approaches and industry-specific considerations.